Moderation Of Pesantren-Based Religious Education Curriculum (Study At Al-Ishlah Assuyuthi Pesantren Dlopo Karangrejo Ngasem Kediri) - M. Luqman Khakim (International Journal of Religion and Social Community, 2023)
In terms of renewal of Al-Ishlah Assuyuthi Pesantren, educational moderation has been carried out, both in terms of institutional organization, learning methods and curriculum. This is done with the intention of meeting the needs of the community for religious education and developing Islamic teachings that are more universal and accommodating. The aim is to find out the implications of moderation of the boarding school-based religious education curriculum at Al Ishlah As Suyuthi Pesantren. The research method uses a qualitative approach with descriptive research type and case study. The research was conducted at Al Ishlah As Suyuthi Pesantren. Data sources are people, place, and paper. Data collection techniques used were observation, interviews, and documentation. The analysis uses data reduction, data presentation and conclusion drawing. The results of this study reveal that: 1). Al Ishlah As Suyuthi Pesantren tries to transform its curriculum, by accommodating the 9-year Wajar Dikdas and accepting the curriculum of the Ministry of Religion, as a step towards moderating the curriculum there are several educational systems, including; Madrasah Diniyah Salafiyah; Tahfidzul Qur'an Program; Wajar Dikdas Wustha; Orphan Education and Routine Recitation of the Yellow Book by promoting inclusive values that teach wasathiyah Islam based on ahlu sunnah wal jamaah 2). The implications of moderation of the education curriculum are more emphasized on the moral-spiritual aspect. This means that the spiritual values of santri as indicated in diligent worship behavior; congregational prayer, qiyamullail, sunnah fasting and so on are more emphasized, the morality aspect as the basic capital of santri in salaf pesantren in preserving the teachings of salafusholih scholars who prioritize religious tolerance values.